The Role of School and Business Collaboration and the Industrial World (DU/DI) in Improving the Competence of Vocational School Students in Banda Aceh City - Riski Sahira Violinda; Nasir Usman; Niswanto (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
This study aims to analyze the school's collaboration with the Business World and the Industrial World (DU/DI) in improving the competence of vocational school students in Banda Aceh City, including cooperation programs, implementation, evaluation, as well as supporting and inhibiting factors. The research used a qualitative approach with 12 informants consisting of school principals, vice principals for public relations and curriculum, heads of expertise programs, and students from SMK Negeri 2 Banda Aceh and SMK Negeri 3 Banda Aceh. Data collection techniques were carried out through semi-structured interviews, observations, and documentation. Data analysis uses the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawing and verification. The results of the study show that cooperation planning is carried out systematically through the identification of competency needs, mapping of industry partners, and curriculum synchronization. The implementation is realized through street vendor programs, teaching factories, student debriefing, and teacher training, with a positive impact on improving students' hard skills and soft skills. Evaluations are carried out regularly through joint meetings, student reports, and feedback from industry. The main supporting factors include school commitment, smooth communication, and principal support, while the biggest inhibiting factors are student unpreparedness and the difference in needs between schools and industry. It is concluded that effective collaboration requires strengthening student readiness and continuously adjusting the curriculum according to the needs of the world of work